Legal Protection of the Medical Code of Ethics in Resolving Health Disputes Between Doctors and Patients - Hidayati Hidayati; Aripin Aripin (Syntax Corporation Indonesia, 2024)
A doctor is a person who has trained in a way professional For help people in need maintenance health in accordance with Human Rights Embodied man with various way, one of them through practice medicine. The purpose of study This is For give protection law code ethics facing medicine with dispute health moment do action medical. Focus study This is about How protection law solution dispute medical between doctor with patient or family. This research uses a normative juridical method using secondary data which is analyzed descriptively. The research results used for know and get description comprehensive with see related facts with problem so that can prove and discover scientific solution _ show that treating doctor dispute medical with patients in hospitals have right For get protection law. Law no. 29 of 2004 concerning Practice Medicine and Law no. 36 years old 2014 regarding Health Workers no give adequate protection for doctor in solution dispute medical between doctor and patient. This is because investigator police will use procedures or procedures in the Criminal Procedure Code when handle case conjecture malpractice, on the other hand UUPK involves institution profession medical do work they in accordance with standard profession a the doctor did it work they in accordance with standard profession, service, and procedures operational entitled on protection law .